APPLICATION OF THE CRT (CULTURALLY RESPONSIVE TEACHING APPROACH IN IMPROVING THE PERSONAL LETTER WRITING SKILLS OF STUDENTS OF STATE SENIOR HIGH SCHOOL 2 LHOKSEUMAWE, ACEH - T. Muntazar; Meri Hari Yanni; Mawardi (RADJA PUBLIKA, 2021)
This study aimed to investigate the effectiveness of the Culturally Responsive Teaching (CRT) approach in enhancing the personal letter-writing skills of high school students. A classroom action research design was employed with a sample of Class X students at SMA Negeri 2 Lhokseumawe. Data were collected through observations, assessments of personal letter-writing skills, and photo and video documentation. Both qualitative and quantitative descriptive analyses were conducted. The findings revealed a significant improvement in students' personal letter-writing skills across all assessed aspects following the implementation of the CRT approach. Specifically, in Cycle 1, 64.51% of students demonstrated incomplete letter-writing skills. However, in Cycle 2, this percentage decreased to 19%, with 81% of students achieving complete letter-writing skills. These results demonstrate the efficacy of the CRT approach in improving the personal letter-writing abilities of Class X students at SMA Negeri 2 Lhokseumawe